Effect of conditioning methods on the microtensile bond strength of phosphate monomer-based cement on zirconia ceramic in dry and aged conditions - Amaral, Regina [UNESP] (2008)
The objective of this study was to evaluate the durability of bond strength between a resin cement and aluminous ceramic submitted to various surface conditioning methods. Twenty-four blocks (5 x 5 x 4 mm3) of a glass-infiltrated zirconia-alumina ceramic (InCeram Zirconia Classic) were randomly divided into three surface treatment groups: ST1 - Air-abrasion with 110-μm Al2O3 particles + silanization; ST2 - Laboratory tribochemical silica coating method (110-μm Al2O3, 110-μm silica) (Rocatec) + silanization; ST3 - Chairside tribochemical silica coating method (30-μm SiOx) (CoJet) + silanization. Each treated ceramic block was placed in its silicone mold with the treated surface exposed. The resin cement (Panavia F) was prepared and injected into the mold over the treated surface. Specimens were sectioned to achieve nontrimmed bar specimens (14 sp/block) that were randomly divided into two conditions: (a) Dry - microtensile test after sectioning; (b) Thermocycling (TC) - (6,000x, 5-55°C) and water storage (150 days). Thus, six experimental groups were obtained (n = 50): Gr1-ST1 + dry; Gr2-ST1 + TC; Gr3-ST2 + dry; Gr4-ST2 + TC; Gr5-ST3 + dry; Gr6-ST3 + TC. After microtensile testing, the failure types were noted. ST2 (25.1 ± 11) and ST3 (24.1 ± 7.4) presented statistically higher bond strength (MPa) than that of ST1 (17.5 ± 8) regardless of aging conditions (p < 0.0001). While Gr2 revealed the lowest results (13.3 ± 6.4), the other groups (21.7 ± 7.4-25. 9 ± 9.1) showed statistically no significant differences (two-way ANOVA and Tukey's test, α = 0.05). The majority of the failures were mixed (82%) followed by adhesive failures (18%). Gr2 presented significantly higher incidence of ADHESIVE failures (54%) than those of other groups (p = 0.0001). Both laboratory and chairside silica coating plus silanization showed durable bond strength. After aging, air-abrasion with 110-μm Al2O3 + silanization showed the largest decrease indicating that aging is fundamental for bond strength testing for acid-resistant zirconia ceramics in order to estimate their long-term performance in the mouth. © 2007 Wiley Periodicals, Inc.